Determinants of Flip.id Usage Intention: Usefulness and Ease Perceptions - Hikmah, Ainun; Al Muizzuddin Fazaalloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
This study is intended to analyze the extent to which the influence of the perception of expediency and perception of convenience to the interest in the use of applications Flip.id at the University of Brawijaya students. The approach used is quantitative with the method of data collection through the distribution of questionnaires to students of FEB Universitas Brawijaya. Sampling technique is done by purposive sampling, which is the selection of respondents based on certain criteria, namely active students who have used the application Flip.id. The number of samples was determined using the Slovin formula so that a sample of 100 respondents was obtained. Data analysis techniques applied are descriptive statistical analysis and PLS-SEM analysis conducted with the help of SmartPLS version 4.0. The results showed that the perception of expediency and the perception of convenience has a positive and significant influence on the interest in using the application Flip.id. The practical implications of these results suggest that managers Flip.id it is necessary to strengthen the aspects of expediency and ease in the development of application features and design, as well as education on active use in the campus environment.